A novel experimental facility for measuring internal flow of Solid-liquid two-phase flow in a centrifugal pump by PIV. (March 2017) - Shi, Baocheng; Wei, Jinjia; Zhang, Yan
Highlights: A novel PIV test facility without agitating was designed. The facility has high accuracy for two-phase flow measurement. Velocity distribution agree with predicted by potential flow theory. Solid-particles has influence on large-scale turbulence structures. Abstract: PIV is one of the most effective flow measurement methods, but for solid-liquid two-phase flow in a centrifugal pump with complex internal structure and high speed rotation, many problems exist in the experimental facility design, such as solid particle releasement, synchronization issues among camera, laser and pump impeller, and methods of avoiding introducing bubbles into flow passage, etc. To solve these critical problems, a new experimental facility without agitation was designed for internal solid-liquid two-phase flow test in a centrifugal pump by PIV. The facility was tested by measuring two-phase flow of water-glass beans and water-rape seeds in a centrifugal slurry pump. The new test facility has many obvious advantages, such as the simpler structure without the agitating device, less noise in the test process, less power consumption, less number of particles to get a certain particle volume concentration, and the decrease of the experiment cost. The result shows that the new facility can realize a stable solid-liquid two-phase flow measurement with high reliability in a centrifugal pump.